Latino-white disparities in ICD-coded asthma diagnosis among US children. (15th February 2022) - Heintzman, John; Ezekiel-Herrera, David; Bailey, Steffani R.; Garg, Arvin; Lucas, Jennifer; Suglia, Shakira; Cowburn, Stuart; Puro, Jon; Marino, Miguel
Abstract: Introduction: It is uncertain if disparities in asthma diagnosis between Latino and non-Hispanic white children stem from differences in diagnosis over time among children presenting with similar clinical scenarios suggestive of asthma. Methods: We evaluated the odds of International Classification of Disease (ICD)-coded asthma diagnosis in Latino (English and Spanish preferring) and non-Hispanic white children, overall ( N = 524, 456) and among those presenting with possible asthma indicators ( N = 85, 516) over a 13-year period, using electronic health record data from a multi-state network of community health centers. Results: Among those with possible asthma indicators, Spanish-preferring Latinos had lower adjusted odds of ICD-coded asthma diagnosis compared to non-Hispanic whites (OR = 0.87, 95%CI = 0.77-0.99); English-preferring Latinos did not differ from non-Hispanic whites. Differences in ICD-coded diagnosis between ethnicity/language groups varied by presenting symptom. Conclusions: Spanish-preferring Latino children may be less-likely to have ICD-coded asthma documented in the EHR when presenting with certain clinical indicators suggestive of asthma. Clinicians should be cognizant of the need for the follow-up of these indicators in Spanish-preferring Latino children.